2019
DOI: 10.1523/eneuro.0304-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

The TRPA1 Ion Channel Contributes to Sensory-Guided Avoidance of Menthol in Mice

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…We also found that application of HC-030031 has weaker inhibitory effects on dTRPA1 currents than previously reported for mammalian isoforms [61]. This is consistent with HC-030031 having species-dependent effects, inhibiting the human, In regard to menthol, the well-documented activation of mouse TRPA1 induced by this compound [31,33] can readily explain the implication of this channel in the aversive behavior of mice to menthol in a drinking assay [52]. In contrast, the scenario in Drosophila is not so clear, as the precise role of dTRPA1 in menthol-induced aversion during oviposition [40] and nocifensive responses of larvae towards direct contact [34] remained unexplored.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that application of HC-030031 has weaker inhibitory effects on dTRPA1 currents than previously reported for mammalian isoforms [61]. This is consistent with HC-030031 having species-dependent effects, inhibiting the human, In regard to menthol, the well-documented activation of mouse TRPA1 induced by this compound [31,33] can readily explain the implication of this channel in the aversive behavior of mice to menthol in a drinking assay [52]. In contrast, the scenario in Drosophila is not so clear, as the precise role of dTRPA1 in menthol-induced aversion during oviposition [40] and nocifensive responses of larvae towards direct contact [34] remained unexplored.…”
Section: Discussionsupporting
confidence: 89%
“…In regard to menthol, the well-documented activation of mouse TRPA1 induced by this compound [25,27] can readily explain the implication of this channel in the aversive behavior of mice to menthol in a drinking assay [47]. In contrast, the scenario in Drosophila is not so clear, since the precise role of dTRPA1 in menthol-induced aversion during oviposition [39] and nocifensive responses of larvae towards direct contact [28] remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The tested concentration of menthol stimulates lingual trigeminal fibers (Lundy and Contreras, 1995) and its oral sensation is not avoided by mice. In an orosensory setting, wild-type mice show only a mild reduction in licking 1.28 mM menthol compared to water (Lemon et al, 2019).…”
Section: Optical and Electrical Stimulimentioning
confidence: 97%
“…AITC engages nociceptors expressing TRP ankyrin 1 (TRPA1) and stimulates TRPV1 at high concentrations (Jordt et al, 2004;Everaerts et al, 2011). Whereas 0.1 mM AITC causes a moderate reduction in licking compared to water in mouse orosensory tests, 1 mM AITC elicits near-zero licks and strong aversion (Lemon et al, 2019).…”
Section: Optical and Electrical Stimulimentioning
confidence: 99%
See 1 more Smart Citation